Dimensions of Gender Construction and Its Implications in Promoting Women’s Empowerment Policies - Ashari, Ashari (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
Gender social construction is a construction that is traditional and processed as a formation through social interaction and cultural norms in society. Gender identity is not solely determined by biological aspects, but is constructed by the social environment. This article aims to describe the gender construction formed in various aspects of community life, as part of an effort to encourage women's empowerment policies. This study employs a qualitative method with a literature review approach to analyze social conceptualization in depth, drawing on various relevant literature. The results of the study indicate that gender construction has a significant impact on gender inequality. However, gender construction is dynamic and can change. By understanding the process of gender construction formation and its impacts, society is expected to be able to educate, encourage women's empowerment policies, as an effort to create fairer, more equal and more dignified gender relations.